Assessment of Cox2 and CMV in patients with chronic HCV infection - F. Hassan, Heba; M. Khashman, Basim; A. Abdul Qader, Omer; W. Izzat, Alaa (Nab'a Al-Hayat Foundation for Medical Sciences and Health Care, Iraq, 2017)
Objective This study was established to determine the expression of COX-2 and CMV in patients with chronic C infection. Methods A total of 30 formalin-fixed of paraffin-embedded liver samples obtained from patients with chronic hepatitis C infection. In addition, 30 apparently normal liver autopsies were used as control group used for immunohistochemistry technique (IHC) to study the expression of cyclooxygenase (COX-2) and cytomegalovirus (CMV) in these samples. Results In current study, the results of expression of COX-2 were found in 25 cases (83.3%) of chronic HCV were strongly positive with a significant increase at P < 0.001, while the result of CMV expression was detected as brown cytoplasmic membranous staining of cells with positive CMV expression demonstrated in 21 (70.0%) out of 30 cases of chronic HCV infection cases. All control groups were negative for the expression of COX-2 and CMV. Conclusion This study concludes that COX-2 and CMV participates in the pathogenesis of chronic HCV infection. Keywords chronic HCV infection, cyclooxygenase (COX-2), cytomegalovirus (CMV)